Assessment of logistics potential in the development of Kazakhstan's food belt - Kaskataev, N.M.; Zholmukhanova, A.Zh.; Koitanova, A.Zh. (BUKETOV BUSINESS REVIEW, 2017)
The problems of the sphere of circulation are considered in the article such as: determination of a system of optimal proportions between the volumes of production, warehousing and transportation; Cost saving from avalanche-like growth of losses in case of failures. And downtime; Establishment of a rational level of cooperation in the system itself Production, storage and transportation; Formation of a rational structure of management information flows without delay in relation to the production process. The authors also analyzed the main directions in the development of the country's transit potential Strategy Kazakhstan-2050 and the new economic policy Nurly Zhol. As a result, Kazakhstan will not only increase the investment attractiveness of the regions, but also the development of the economy of the regions, the reduction of transport and logistics costs, the development of the market for transport and logistics services in the regions, the creation of new jobs, and the transit potential of the country. Within the framework of the considered regional differentiation of the gross regional product per capita, we can note a significant gap in this indicator between the regions with the raw material structure of the economy and regions oriented towards light industry, agriculture, etc. The results of the analysis make it possible to state that the raw material regions in terms of indicators Production of gross output, including per capita, are in a much better position than regions that have a different raw material Th specialization. As can be seen from the results of the analysis, the current sectoral structure of the economy has a direct impact on the social and economic situation, the living standards of the population of the regions, the magnitude of the gross value added generated by the analyzed regions.